2014
DOI: 10.1534/genetics.114.163063
|View full text |Cite
|
Sign up to set email alerts
|

Clinal Variation at Phenology-Related Genes in Spruce: Parallel Evolution in FTL2 and Gigantea?

Abstract: Parallel clines in different species, or in different geographical regions of the same species, are an important source of information on the genetic basis of local adaptation. We recently detected latitudinal clines in SNPs frequencies and gene expression of candidate genes for growth cessation in Scandinavian populations of Norway spruce (Picea abies). Here we test whether the same clines are also present in Siberian spruce (P. obovata), a close relative of Norway spruce with a different Quaternary history. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 83 publications
(103 reference statements)
8
67
1
Order By: Relevance
“…For instance, by selecting candidates from studies not only in maritime pine but also in other conifers, we assumed that adaptive processes mostly occur by convergent evolution in the same set of genes, while there is evidence suggesting that species adaptation to identical environments may involve separate genes and a certain number of possible paths (e.g., Tenaillon et al 2012). For example, only 2 of the 18 genes surveyed in latitudinal clines of two Eurasian boreal spruces showed identical associations with bud phenology (Chen et al 2012(Chen et al , 2014, while only 3 outlier genes related to climate were shared between two sympatric Picea species in eastern Canada (Prunier et al 2011). Similar results have been reported for adaptation to freshwater in sticklebacks (Deagle et al 2012) and to high elevation in humans (Bigham et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, by selecting candidates from studies not only in maritime pine but also in other conifers, we assumed that adaptive processes mostly occur by convergent evolution in the same set of genes, while there is evidence suggesting that species adaptation to identical environments may involve separate genes and a certain number of possible paths (e.g., Tenaillon et al 2012). For example, only 2 of the 18 genes surveyed in latitudinal clines of two Eurasian boreal spruces showed identical associations with bud phenology (Chen et al 2012(Chen et al , 2014, while only 3 outlier genes related to climate were shared between two sympatric Picea species in eastern Canada (Prunier et al 2011). Similar results have been reported for adaptation to freshwater in sticklebacks (Deagle et al 2012) and to high elevation in humans (Bigham et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…; Chen et al . ; Table S1, Supporting information) and completed the sampling by adding 20 new populations from hitherto poorly characterized areas such as northeast Russia, the Ob River area and regions east of the Yenisei River (Fig. A; Table S1, Supporting information).…”
Section: Methodsmentioning
confidence: 99%
“…Population genetic approaches have revealed several examples of convergent local adaptation at the molecular level: within the threespine stickleback (Gaterosteus aculeatus) the EBT locus has been involved in repeated adaptation to freshwater habitats [31], two species of European spruce harbor adaptive latitudinal clines at Ft2 and GI genes [32], and EPAS1 and HBB genes show patterns of high altitude adaptation in both dogs [33] and Tibetan humans [34]. Chen et al [32,36] identified a total of 18 genes harboring SNPs with signatures of latitudinal adaptation in the two species but only 2 genes were detected in both species, and Wang et al [33] identified 14 genes with strong signatures of high altitude adaptation in dogs but only 2 targeted in both dogs and humans. Moreover, the EPAS1 locus does not appear to have been the target of selection in Andean populations [37].…”
Section: Is Local Adaptation Convergent At the Molecular Level?mentioning
confidence: 99%